ОРГАНІЗАЦІЯ ВИСТАВОК ЯК ВИД НАУКОВО-ТВОРЧОЇ ДІЯЛЬНОСТІ МАЙБУТНІX ХУДОЖНИКІВ-ПЕДАГОГІВ (Педагогіка вищої та середньої школи, 2006)
In the article a question is considered about the role of exhibition activity in the system of artistically-pedagogical education and councils are expounded of organization of artistic exhibition.